Lessons Learned While Completing a Needs Assessment of ITSS, Inc. Career Development Opportunities: A Case Study. Issue 4 (19th January 2016) - Aull, Janice; Bartley, Jeff; Olson, Colleen; Weisberg, Lauren; Winiecki, Donald
Abstract: ITSS, Inc. (a pseudonym), a leading provider of IT solutions and services in North America, provides a career development program to its 7, 000 employees. Recent data collected through surveys and utilization reports indicated lower than desired satisfaction levels with the organization's various career development tools, resources, and programs, as well as with participation in those programs. This was a concern for ITSS, which asserts that its employees' knowledge, skills, and attitudes are a competitive advantage. In response, the organization engaged a team of graduate students to examine potential performance issues arising from these observations. As a first‐level priority, we identified a performance gap regarding the current structure of the organization's career development program. Next, we launched a full needs assessment to uncover the root causes of the performance gap. Last, we identified and suggested interventions to improve performance‐based outcomes for the organization. This study highlights the systematic and systemic approach we employed to define the performance outcomes and gap, analyze the causes, and align the most effective solutions to close the gap and support the organization's goals. * In addition to describing this case study in needs assessment, this article provides reflective descriptions of the actual process of sketching out the basic framework of the project, which included deciding how to use certain assessment methods, choosing informants, collecting and analyzing data, and arriving at findings and interventions. The goal of this added layer of information is to provide readers with a behind‐the‐scenes look at the process of a needs assessment, with the aim of demonstrating how needs assessments, like dedicated academic research, require inductive, deductive, and abductive thinking to provide value to the client organization.